2004
DOI: 10.1111/j.1440-1770.2004.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for the complicated occurrence of nuisance odours from phytoplankton and environmental factors in a eutrophic lake

Abstract: Odours in waters used for various purposes, especially musty odours, is a worldwide problem. To establish an early warning system, the nuisance odour in an aquatic environment, the causative microorganisms and compounds, and the mechanism of odour in Lake Kasumigaura, the second biggest lake in Japan, were examined using in situ studies. In this study, the mechanism for the occurrence of musty odours was determined, and the level of musty odour was discriminated, based on 32 months of phytoplankton data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 16 publications
(12 reference statements)
0
27
1
Order By: Relevance
“…Quantification of cyanobacteria mic copies in Lushui Reservoir and Donghu Lake revealed no linear correlation between the abundances of potential MIB-producing cyanobacteria and total cyanobacterial biomass (dominant groups), which was different from the conclusions obtained by previous studies demonstrating the clear relationship between cyanobacterial biomass and T&O problems (Dzialowski et al 2009;Jüttner and Watson 2007;Sugiura et al 2004). Therefore, abundances of MIB-producing cyanobacteria should be the determinant for T&O prediction instead of cyanobacterial biomass because of its uncertain relationship with odor concentration.…”
Section: Discussioncontrasting
confidence: 55%
“…Quantification of cyanobacteria mic copies in Lushui Reservoir and Donghu Lake revealed no linear correlation between the abundances of potential MIB-producing cyanobacteria and total cyanobacterial biomass (dominant groups), which was different from the conclusions obtained by previous studies demonstrating the clear relationship between cyanobacterial biomass and T&O problems (Dzialowski et al 2009;Jüttner and Watson 2007;Sugiura et al 2004). Therefore, abundances of MIB-producing cyanobacteria should be the determinant for T&O prediction instead of cyanobacterial biomass because of its uncertain relationship with odor concentration.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, Dzialowski et al [13] constructed models for dissolved geosmin (d-GEO) in the drinking water reservoirs of Kansas (USA) using several abiotic factors and four cyanobacterial genera. Sugiura et al [22] developed predictive models for dissolved 2-methylisoborneol (d-MIB) and d-GEO using data on abiotic environmental parameters and 25 genera of phytoplankton collected from Lake Kasumigaura (Japan). However, there are still many unknowns concerning the development of predictive models for the T&O compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dzialowski et al (2009) found that cyanobacterial biovolume is not a consistent predictor of dissolved geosmin, and Durrerl et al (1999) indicated that correlations between a particular taxon and particle-bound geosmin cannot be expected to occur in any instance in natural waters. On the contrary, a few researchers observed positive correlation between geosmin and cyanobacterial biovolume (Jüttner and Watson, 2007;Sugiura et al, 2004). Li et al (2007) suggested that dissolved odorous compounds are affected by various factors, such as rate of odor production by algal cells, biodegradation by microbes, photolysis by sunlight, absorption by particles, disturbance by wave and volatilisation of odorous compounds themselves.…”
Section: Algal Biomass and MC Concentrationmentioning
confidence: 99%